Mga titik at himig words and music. - Acoymo, Ramon (G.A.C. Prod., 2001)
This compact disk combines poetry and music representing the highest aspirations and endeavors of the Filipino soul. The first two songs date to the Philippine revolution and although their creative origins cannot be determined with certainty the fervor for freedom they embody is still palpable. The songs of the Panggasinense, Pampango and Waray languages are based upon traditional poetry. The four art songs set to poetry of Rofel Brion were given their world premiere by Ramon Acoymo in recital in the year 2000. The final song is a most fitting prayerful tribute to the source and inspiration of all human creation.